The Impact of the Learning Organization on Product Innovation Performance: an Empirical Assessment in the French Biotechnology Industry - Hannachi, Yacine (Management international / International Management / Gestiòn Internacional, 2016)
This paper examines the role played by the learning organization culture in generating product innovation performance. It also aims at assessing the moderating effects of environmental turbulence, export intensity and public innovation support on the aforementioned relationship. We use structural equations modeling with partial least squares technique to test our hypotheses on a data set from the French biotechnology industry. The results generally support theoretical predictions and emphasize the key role that learning organization has for product innovation performance.